Sports and students’ mental wellness / Muhammad Zarif Hakimi Mohamad Asri …[et al.] - Mohamad Asri, Muhammad Zarif Hakimi; Adnan, Imran Hakim; Mohd Arif, Muhammad Syahmi; Kamaludin, Luqman Hakim (Universiti Teknologi MARA (UiTM), 2020)
Many people around the world experience stress irrespective of their age, race, religion, color, profession, academic background or surrounding environment (Esia-Donkoh, Yelkpieri & EsiaDonkoh, 2011). Some of the people tend to do physical activities to reduce the stress level that they felt. This is because they can reduce stress by getting themselves joining outdoor and indoor activities such as jogging, badminton, bowling, swimming and so on. The activities will help them to stimulate the production of endorphins in the bloodstream. This study is focusing on the universities students because nowadays students tend to get stress during to overtime study and the load of assignment given by their lecturer. Besides, students are currently studying online which is some of the students’ family did not understand how the class is working. Some of the students also did not have the facilities to join the online study which prevent them to get information from the classes. Students need to thinks some ways to help them reduce the stress level because it is not good for their mental health. However, there are also some of the students that have all the facilities needed for the online classes but they still take advantage by giving may excuses during the online classes. Universities students need to make sure that their mental health is in a great condition during this online classes because the online classes also are challenging if they did not prepare for the worst to happen. One of the ways to reduce the stress level is doing exercise. Students need to identifies which exercise and sports that suitable with them in order for the students to get their mental health stable. Since they are currently studying online, they can just do a simple workout in their house. The endorphins released by doing the workouts can trigger positive feeling in the body. Apart from that, exercise also can increase energy levels which enable the students to give more focus in their online study. Students can improve their sleep quality by doing the exercise because they are often to have a messy schedule of sleeping. Sports and exercise are proven to give many benefits and advantages to the students not only to their mental health but also to their physical health.